A biomimetic multi-component subunit vaccine via ratiometric loading of hierarchical hydrogels - Fanfan Du; Simseok A. Yuk; Yuan Qian; El Hadji Arona Mbaye; Michael P. Vincent; Sharan Bobbala; Tirzah M. Abbott; Hyeohn Kim; Yang Li; Haoyu Li; Sijia Yi; Baofu Qiao; et al. (Nature Communications)
Abstract The development of subunit vaccines that mimic the molecular complexity of attenuated vaccines has been limited by the difficulty of intracellular co-delivery of multiple chemically diverse payloads at controllable concentrations. We report on hierarchical hydrogel depots employing simple poly(propylene sulfone) homopolymers to enable ratiometric loading of a protein antigen and four physicochemically distinct adjuvants in a hierarchical manner. The optimized vaccine consisted of immunostimulants either adsorbed to or encapsulated within nanogels, which were capable of noncovalent anchoring to subcutaneous tissues. In female BALB/c and C57BL/6 mice, these 5-component nanogel vaccines demonstrated enhanced humoral and cell-mediated immune responses compared to formulations with standard single adjuvant and antigen pairing. The use of a single simple homopolymer capable of rapid and stable loading and intracellular delivery of diverse molecular cargoes holds promise for facile development and optimization of scalable subunit vaccines and complex therapeutic formulations for a wide range of biomedical applications.